MEREFLEKSIKAN MAKNA SALAFI SECARA LOGIS-FALSAFI: ANTARA ḤAML AL-AWWALĪ ADZ-DZĀTĪ DAN ḤAML ASY-SYĀIʿ ASH-SHINĀʿI - Muhammad Rusydi; Rahmi Rabiaty; Ayu Lestari (Pascasarjana UIN ANTASARI Banjarmasin, 2021)
The term Salafi, at glance, is paradox because the term with the meaning referring to al-Qur’an and the tradition, is held by all Islamic schools, but, when it indicates the certain ideology in Islam with rigid, radical and terror characteristics, other Islamic ideologies avoid it. The term, thus, is interesting to research with offering the following main questions: what is the real meaning of Salafi and how is the term to be constructed as the ideology and sole meaning? Answering this, the research proposes a logical and philosophical approach, especially with the primary essential predication (ḥaml al-awwalī adz-dzātī) and the common technical predication (ḥaml asy-syāīʿ ash-shināʿī) methods.Furthermore, the term Salafi may be delineated as referring to what has been before, mā qad salaf, that is, companion era, followers (Tābiʿūn), and following the followers (Tābiʿ Tābiʿīn) era, according to the primary essential predication. However, the common technical predication shows the variative meaning for Salafi. Some define it with rigid, literal and radical while others accommodate it inclusively, “smoother and more polite”. The contestation among the meaning, then, has constructed the current meaning of Salafi as the school with certain ideology such as literal, radical and rigid characteristics.